BOUNDEDNESS RESULTS FOR SOLUTIONS OF CERTAIN NONLINEAR DIFFERENTIAL EQUATIONS OF SECOND ORDER - Cemil Tunc (IndoMS, 2010)
In this paper, we establish some new sufficient conditions which guaranteethe boundedness and the uniform boundedness of solutions of certain nonlinearand nonautonomous differential equations of second order. By defining appropriateLiapunov functions, we obtain some new results on the subject, and examples arealso provided to illustrate the feasibility of the proposed results. By this work, weextend and improve some boundedness results in the literature.DOI : http://dx.doi.org/10.22342/jims.16.2.35.115-126